(untitled) (Journal of Forensic Medicine & Toxicology, 2017)
Belagavi, the largest district and second capital city of Karnataka is located in the lap of Western ghats surrounded by serene hamlets rich in lush green forest and roaring rivers. In this magnanimous nature Human Animal conflict is a very severe concerned issue, especially with serpents. Hence a retrospective study was conducted to study the snake bite cases admitted to Tertiary Care Hospital at North Karnataka in terms of person, place, time and many more, over a period of one year from 1st January 2014 to 31st December 2014. In the above said period, a total 254 cases were admitted to hospital with history of snake bite. In this 170 cases (67%) were of non poisonous snake bites with male preponderance with 180 cases (70.8%). Highest number of cases was admitted in July month with 60 cases (83.6%) and in monsoon season with 134 cases (59.7%). Most of the bites were inflicted over lower limbs; 172 cases (67.7%) during day time 168 cases (66.1%). The total mortality rates 12 cases (4.7%) with most affected age group were 21-30 years with 70 cases (27.5%).